Флоренция - дочь дьявола: романы : [перевод с польского] / И. Хмелевская - Хмелевская Иоанна (У-Фактория, 1998)
Экземпляры: ф.5 (2003) / Инвентарный номер: 40872 / Цена: / Сис.шифр: 84(4Пол)-4 / Авт.знак: Х 65 / ГРНТИ: 17.82.31 / ББК: 84(4Пол)-44